Small bowel responses to enteral honey and glutamine administration following massive small bowel resection in rabbit (2008)
The trophic effects of honey and glutamine in the healing and adaptation of the small bowel following intestinal resection were studied in some Nigerian non-descript breeds of rabbits. Nine rabbits of mixed sexes with mean body weight of 1.45 ±0.55kg were used. They were randomised into three treatment groups following 50% small bowel resection. Group A rabbits were placed on oral honey treatment. Group B on oral glutamine and group C on normal saline (control). All groups exhibited signs of small bowel adaptation (glutamine(B) honey (A) control (C) at the end of the experiment (4 weeks) with oral glutamine showing the best overall effects on intestinal mucosal growth and adaptation evidenced by significant increase (P<0.05) in residual bow'el length (37.3%), villi width (20.0%), crypt depth (113.3%) and a non significant increase in villus height (33.3%) and cellular mass (10.2%). Honey showed a better effect than control with a significant increase (P<0.05) in villi width (18.2%), crypts depth (66.7%) and cellular mass (33.9%) and a non significant increase in gross residual bow'el length (24.6%), and villus height (30.5%). Our result shows that honey and glutamine have trophic effects on bowel mucosa healing and hyperplasia and have potential therapeutic effects on massive bowel resection in humans